Thermal properties and thermal stability of polypropylene composites filled with graphene nanoplatelets. (February 2018) - Liang, JZ; Wang, JZ; Tsui, Gary CP; Tang, CY
The thermal properties and thermal stability of polypropylene (PP) composites separately filled with graphene nanoplatelets (GNPs) with three different sizes were measured using a differential scanning calorimetry and a thermal gravimetric analyser. The results showed that the values of the melting temperature of the composites were higher than that of the unfilled PP; the thermal stability increased with increasing the weight fraction and lateral dimension of GNPs in the case of low filler concentration, while the effect of the GNPs thickness on the thermal stability was insignificant; the onset decomposition temperature increased with increasing the GNPs lateral dimension, while the maximum thermal decomposition rate increased first and then decreased with increasing the GNPs weight fraction. The thermal stability improvement should be attributed to the sheet barrier function of the GNPs.